Current Methods and Advances in Simulation of Hemorrhage after Trauma. Issue 10 (October 2017) - Bowles, Cayley; Canuto, Daniel; Teran, Joseph; Dutson, Erik; Plurad, David; Eldredge, Jeff; Benharash, Peyman
As animal models fall out of favor, there is demand for simulators to train medical personnel in the management of trauma and hemorrhage. Realism is essential to the development of simulators for training in the management of trauma and hemorrhage, but is difficult to achieve because it is difficult to create models that accurately represent bleeding organs. We present a simulation platform that uses real-time mathematical modeling of hemodynamics after hemorrhage and trauma and visually represents the injury described by the model. Using patient-specific imaging, 3D-mesh representations of the liver were created and merged with an anatomically accurate vascular tree. By using anatomically accurate representations of the vasculature, we were able to model the cardiovascular response to hemorrhage in a specific artery. The incorporation of autonomic tone allowed for the calculation of bleeding rate and aortic pressures. The 3D-mesh representation of the liver allowed us to simulate blood flow from the liver after trauma. For the first time, we have successfully incorporated tissue modeling and fluid dynamics with a model of the cardiovascular system to create a simulator. These simulations may aid in the creation of realistic virtual environments for training.